HUBUNGAN DUKUNGAN DAN PENGETAHUAN SUAMI DENGAN RENDAHNYA PENGGUNAAN KB AKDR (INTRAUTERINE CONTRASEPTIVE DEVICE) - Pasra Monita Naibaho; Vitalia Hanako Murni Simajuntak; Juliana Munte; Srilina Pinem (STIKES Columbia Asia Medan, 2024)
The Family Planning Program (KB) is one of the government's efforts to control population growth and to build quality families. Long-term contraceptive methods, including intrauterine devices (IUDs), are part of the government program, but their usage remains low. One of the reasons is the lack of support and knowledge from husbands. Husband’s support is a crucial form of motivation for wives in using contraceptives. The more knowledge and information the husband has, the more support he can provide to his wife in using IUD contraception. This study aims to determine the relationship between husband’s support and knowledge with the low usage of IUD contraception at PMB Linda Elisabet in Kemiri Muka Subdistrict, Depok City, West Java, in 2024. This research is an analytic survey with a cross-sectional design. The population in this study is the husbands of women who use contraceptives, and the sample consists of 10 individuals selected through non-probability sampling or total sampling. Data were analyzed using the Chi-square test (α=0.05). The results show that the majority of wives do not use IUDs (76.5%), while only 23.5% do. The statistical chi-square test showed a significant relationship between husband’s support and knowledge with the low usage of IUD contraception at PMB Linda Elisabet in Kemiri Muka Subdistrict, Depok City, West Java, with a p-value of 0.003 (P<0.05). In conclusion, there is a significant relationship between husband’s support and knowledge and the low usage of IUD contraception at PMB Linda Elisabet in Kemiri Muka Subdistrict, Depok City, West Java, in 2024. The more knowledgeable the husband, the greater his support for his wife in using IUD contraception. Health workers should regularly provide counseling on the importance of IUD contraception, and husbands are expected to increase their knowledge. With greater knowledge of IUD contraception, husbands can provide more support to motivate their wives to use it.